2010
DOI: 10.1210/jc.2010-0537
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Pituitary Adenomas in Northern Finland in 1992–2007

Abstract: The final cohort consisted of 355 PAs. The incidence rates of the Oulu University Hospital regional district were used as a reference to assess the applicability of our case finding over the rest of NFi. Incidence rates of all PA subgroups except microprolactinomas were statistically equal between these areas; thus, all presented SIRs are based on the NFi's cohort except Oulu University Hospital regional district-based prolactinomas and PAs overall. Overall SIR of PAs was higher (4.0 per 100,000) than in previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
262
11
27

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(332 citation statements)
references
References 18 publications
32
262
11
27
Order By: Relevance
“…The greater number of females in this study may be due to general female preponderance of meningiomas and pituitary adenomas. 1,3,8,13,14,15 The disparity in sex distribution between this study and the Nigerian studies may also be attributed to the bulk (83.3%) of tumours in this study being meningiomas and pituitary adenomas whereas this group of tumours constituted 52.1% and 39.8% in Onapoya's 2 and Idowus's series 13 respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…The greater number of females in this study may be due to general female preponderance of meningiomas and pituitary adenomas. 1,3,8,13,14,15 The disparity in sex distribution between this study and the Nigerian studies may also be attributed to the bulk (83.3%) of tumours in this study being meningiomas and pituitary adenomas whereas this group of tumours constituted 52.1% and 39.8% in Onapoya's 2 and Idowus's series 13 respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…Clinical manifestations of pituitary adenomas imply a much lower prevalence. A series of studies on well-defined populations report a prevalence of 75.7-94/100 000 inhabitants of clinically overt cases (30,31,32), and the reported incidence is 3.9-4.1 cases/100 000 inhabitants per year (31,33,34). Pituitary adenomas are one of the most frequently occurring intracranial tumors, and the occurrence of pituitary adenomas seems to be similar despite geographic or ethnic differences (29,35,36).…”
Section: Epidemiologymentioning
confidence: 99%
“…TSHomas are the rarest among the pituitary adenomas, only representing 0.7-0.94% of all pituitary adenomas (31,33,34). A comprehensive study of the Swedish national Pituitary Registry found a national prevalence of 2.8 clinically overt cases per million inhabitants and an incidence rate of 0.15 cases per million inhabitants per year (19).…”
Section: Epidemiologymentioning
confidence: 99%
“…Prolactinomas are the most frequent pituitary tumors, with a prevalence estimated to be 35-60 cases per 100 000 individuals (1,2,3). Women are predominantly affected and generally have symptoms of hypogonadism and/or galactorrhea (4,5), whereas men are more likely to present with larger adenomas at the time of diagnosis and show drug resistance (6).…”
Section: Introductionmentioning
confidence: 99%